Cancer‐Specific Therapy by Artificial Modulation of Intracellular Calcium Concentration. Issue 18 (31st July 2019) - Wang, Cheng; Yu, Fangying; Liu, Xuerong; Chen, Shaoqing; Wu, Rui; Zhao, Rui; Hu, Fuqiang; Yuan, Hong
Abstract: Calcium (Ca 2+ ) hemeostasis is crucial for the normal function of cellular biochemistry. The abnormal frequency of Ca 2+ signaling in cancer cells makes them more vulnerable to Ca 2+ modulation than normal cells. Here in this study, a novel cancer‐specific therapy by artificially triggering Ca 2+ overload in cancer cells is proposed. The feasibility of this therapy is illustrated by successful coupling of selective extrusion (Ca 2+ ) inhibition effect of Curcumin (Cur) and the effective Ca 2+ generating capability of amorphous calcium carbonate (ACC) into a facilely prepared water responsive phospholipid (PL)–ACC hybrid platform (PL/ACC–Cur). The obtained results demonstrate that PL/ACC–Cur can specifically boost the intracellular Ca 2+ concentration to cause Ca 2+ overload and to trigger mitochondria‐related apoptosis in MCF‐7 cells while sparing normal hepatocyte (L02), which might be a promising approach for effective cancer therapy. Abstract : A novel cancer‐specific therapy by artificially triggering Ca 2+ overload in cancer cells is proposed. The feasibility is illustrated by coupling the extrusion (Ca 2+ ) inhibition of Curcumin (Cur) and effective Ca 2+ generating of amorphous calcium carbonate (ACC) into a phospholipid (PL)‐ACC hybrid platform (PL/ACC‐Cur). PL/ACC‐Cur can selectively induce Ca 2+ overload and trigger mitochondria‐related apoptosis in MCF‐7 cells.